THE EFFECT OF SPECIAL EXERCISES TO DEVELOP RAPID STRENGTH AMONG JUNIOR FOOTBALL PLAYERS AGED (12-14) YEARS (American Journal of Research in Humanities and Social Sciences, 2023)
The objective of this study was to examine the impact of the Special Exercises To Develop Rapid Strength training method on individuals aged 12-14 years old who are novice football players. The study aimed to evaluate both the theoretical and practical aspects of this training method in order to determine its effectiveness and suitability for this specific age group. The study aimed to prepare special exercises to develop the rapid strength of football players junior age (12-14) years and the researcher assumed that there are statistically significant differences between the results of the pre- and post-tests of the two groups (experimental and control) and in favor of the experimental group, The researcher used the experimental approach to achieve the objectives of the research and contribute to solving the research problem, the research sample included (24) players from the oil club players within the participating teams. The sample of this research included 24 total players, during a pilot program in a Al-Naft Club. The program lasted 4 weeks, from 16 of September until 12 of December and the workouts occurred in frequency, 3 trainings per week, enduring 90 minutes each one. In order to realize this research, we used four reliable tests, which are the following: a) Forward Support Test, b) Three Partridges Right and Left Test, c) Medical Ball Push Test, d) Vertical Jump Test of Stability. These tests have been used by many researchers and are analyzed below. For the statistical analysis, we used paired samples t-test in order to compare two averages and for the analysis we used statistical software SPSS20. the league championship and the results of the tests showed the effectiveness of physical exercise to develop the rapid strength of the players of the Al-Naft Club junior category.